2014
DOI: 10.1186/1471-2407-14-860
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and lung cancer: a case control study in Iran

Abstract: BackgroundDespite many prospective and retrospective studies about the association of dietary habit and lung cancer, the topic still remains controversial. So, this study aims to investigate the association of lung cancer with dietary factors.MethodIn this study 242 lung cancer patients and their 484 matched controls on age, sex, and place of residence were enrolled between October 2002 to 2005. Trained physicians interviewed all participants with standardized questionnaires. The middle and upper third consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Recently, there has been increasing interest in their use to prevent, mitigate or treat specific diseases . The associations of risk relating to cancer with fermented dairy foods intake have already been widely studied . However, the results remained inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been increasing interest in their use to prevent, mitigate or treat specific diseases . The associations of risk relating to cancer with fermented dairy foods intake have already been widely studied . However, the results remained inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggest that all bread eaten in Iran is made with refined flour that contains no bran, indicating a lack of dietary fiber might be a factor in increased risk. However, the data from this study also suggest a number of potential confounders (31). First, those with lung cancer ate fewer fruits and vegetables than control subjects.…”
Section: Series Of Reviews On Carbohydrates Wheat and Cereal Grainsmentioning
confidence: 85%
“…Also, these types of bread production methods potentially can produce smoke and char, which may be associated with increased risk of lung cancer. Another small Iranian case-control study found that those who were in the upper tertiles of bread and rice intakes were associated with an increased risk of lung cancer (31). The authors suggest that all bread eaten in Iran is made with refined flour that contains no bran, indicating a lack of dietary fiber might be a factor in increased risk.…”
Section: Series Of Reviews On Carbohydrates Wheat and Cereal Grainsmentioning
confidence: 99%
“…; Hosseini et al . ). It is a major constituent of several folk medicines and is recommended during pregnancy and breastfeeding.…”
Section: Introductionmentioning
confidence: 97%
“…Yoghurt is a dairy product made by bacterial fermentation of, usually, cow's and sheep's milk (Ramchandran and Shah 2010). Yoghurt butter oil, the fat traditionally derived from yoghurt butter, is one of the most widely consumed fats in India, Iran, Greece, Turkey and several other countries (S ßenel et al 2011;Serafeimidou et al 2012;Hosseini et al 2014). It is a major constituent of several folk medicines and is recommended during pregnancy and breastfeeding.…”
Section: Introductionmentioning
confidence: 99%